There are many ways to solve his problem. The easy one is to do the fowolling.
We take the function of the statement:
Then, we take the first table, then we replace one by one the values of x in the function, for each value we compute the value of y and we make a table. Then we see which table of the statement concides with the table that we computed.
For the first table we have:
x = 1, y = 3*1 - 3 = 0
x = 2, y = 3*2 - 3 = 3
x = 3, y = 3*3 - 3 = 6
x = 4, y = 3*4 - 3 = 9
We see that the table that we computed is the same of the first table of the statement.
So the answer to this problem is: Table 1
Observation: doing his procedure we found the answer directly. It could happen that in another exercise we have different values of x in each table, in that case we must proceed as in this problem, but computing the table as we did for every set of values of x and then compare our result with the correspondent table of the statement.